PENINGKATAN FLUENCY DAN ELABORATION DENGAN MODIFIED FREE INQUIRY - Surur, Agus Miftakus (Institut Agama Islam Negeri Kediri, 2017)
Abstract: Researchers chose a modified free inquiry model to help improve students’ fluency and elaboration. The purpose of this research is to know the application of modified free inquiry which can improve the student’s fluency and elaboration of students’ thinking on trigonometric material. Research method in this research is qualitative research method and research type is research of class action. The data in this study were obtained from the results of validation, test results, observation of teacher and student activity, and interview result, then apply data triangulation and theory to check the validity of data. The results showed an increase in fluency and elaboration in students. This means that a modified free inquiry model can help improve students’ fluency and elaboration in trigonometric learning. The results are supported by the observation of teacher and student activity that is in accordance with the lesson plan and also the result of the interview which get positive response from the students. Abstrak: Peneliti memilih model pembelajaran modified free inquiry untuk membantu meningkatkan fluency dan elaboration siswa. Tujuan penelitian ini adalah untuk mengetahui penerapan modified free inquiry yang dapat meningkatkan fluency dan elaboration berpikir siswa pada materi trigonometri. Metode penelitian pada penelitian ini adalah metode penelitian kualitatif dan jenis penelitiannya adalah penelitian tindakan kelas. Data pada penelitian ini diperoleh dari hasil validasi, hasil tes, hasil observasi aktivitas guru dan siswa, dan hasil wawancara, kemudian menerapkan triangulasi data dan teori untuk pengecekan keabsahan data. Hasil penelitian menunjukkan adanya peningkatan fluency dan elaboration pada siswa. Hal ini berarti model pembelajaran modified free inquiry dapat membantu meningkatkan fluency dan elaboration siswa dalam belajar trigonometri. Hasil tersebut didukung dengan hasil observasi aktivitas guru dan siswa yang sudah sesuai dengan rencana pembelajaran dan juga hasil wawancara yang memperoleh respon positif dari siswa.